State-Region Program Contracts: Instruments of Advanced Regionalization – Challenges and Perspectives for the Fez-Meknes Region - ZMARROU Safaa,; ELJADDAOUI Abdelhakim, (African Scientific Journal, 2025)
Abstract As part of Morocco's Advanced Regionalization (AR), the State-Region Program Contracts (CPER) are crucial for structuring territorial development by tailoring actions to local specificities. However, their implementation is hindered by major challenges. Drawing on New Public Management (NPM), institutional theories, and governance theories, this study explores the dynamics of these contracts through a qualitative analysis within the Fez-Meknes region council. The qualitative study was conducted through semi-structured interviews with 25 senior officials responsible for overseeing CPER projects, document analysis, and observations. This study highlights several key issues in the implementation of the program contracts. Coordination and communication difficulties between actors undermine the effectiveness of the projects, while the lack of financial and human resources, as well as gaps in technical skills, and limit their potential. Moreover, the governance mechanisms and project monitoring systems are insufficient, leading to delays and inefficiencies. Lastly, economic crises and political changes have a significant impact on the stability and continuity of initiatives, complicating their long-term realization. To improve the effectiveness of the CPER, the study recommends a set of criteria including context evaluation, stakeholder mobilization, performance, and flexible governance mechanisms. These recommendations aim to establish contracts that are better suited to regional realities, strengthening inter-institutional coordination. Keywords Advanced Regionalization, Program contract, New Public Management.